Effect of Plant Growth Regulators on in vitro Direct Organogenesis of NEOLAMARCKIA MACROPHYLLA (RED KELAMPAYAN) - Ong, Li Ying (Universiti Malaysia Sarawak (UNIMAS), 2018)
Neolamarckia macrophylla belongs to Rubiaceae family and locally known as red kelampayan. It has increasing demand industrially and economically because of its potential use in fuel-wood products and high timber quality. Due to its versatile properties, it has been depleted in its natural environment. The aim of this study is to determine the effect of different concentrations and combinations of plant growth regulators on direct plant regeneration of N. macrophylla. In this study, the leaves of N. macrophylla are cultured on full strength MS media supplemented with different concentration of Naphthalene acetic acid (1.0, 3.0 and 5.0 mg/L, w/v) in combination with 6-Benzylaminopurine (0.5 mg/L, w/v) for direct root organogenesis and vice versa for direct shoot organogenesis. Percentage of shoot and root formation, number of shoot and root per explant, shoot and root length and percentage of direct organogenesis were analyzed by using one way ANOVA and Duncan's Multiple Range Test in SPSS Version 22. The experimental design used was Randomized Complete Design (CRD). The cultures are maintained at room temperature (25°C f 2°C) with 16 hours light and 8 hours dark photoperiod for 56 DAC. The results had shown that 3.0 mg/L NAA in combination with 0.5 mg/L BAP were found to be the optimal medium for direct root organogenesis, which gave the highest percentage of direct root organogenesis (87.50%). In addition, only low direct shooting response (6.25%) were observed on the MS medium with 1.0 mg/L BAP and 0.5 mg/L NAA.